IMMIGRATION OF VENEZUELAN WOMEN IN BOA VISTA, RORAIMA: FAMILY AND ECONOMIC WITH VENEZUELA - Alessandra Rufino Santos (Revista Tempo do Mundo)
This article deals with the increase of women within the migratory movement of immigrants of Venezuelan nationality in Boa Vista, capital of Roraima. In this migratory process, male participation continues to be dominant and the migratory project changes according to gender. From the female point of view, this study that had the participation of thirteen Venezuelan women highlights their emigration to Brazil as a family project, which includes both family members who stayed in Venezuela and those who also went to Brazil.